You have to do distributive property

Notice that another way to think of negating a number or expression (negating is a fancy way of saying putting a negative sign in front of it) is instead to think of multiplying the number or expression by -1.

E.g. -4 = (-1) * 4

E.g. -(x + y) = (-1)(x + y) = (-1)x + (-1)y = -x + -y = -x - y

-(3k - 12) = -(3k + -12) = (-1)(3k + -12) = (-1)3k + (-1)(-12) = -3k + 12

Although to save time, this can be instead thought of as distributing the negative/minus sign.

-(3k - 12) = -(3k) - -12 = -3k + 12

## Comments